Associations Between Maternal Feeding Styles and Infant Intake of a Lipid Nutrient Supplement. (29th May 2020) - Montalvo, Allyson; Davis, Kathryn; Flesher, Abigail; Moding, Kameron; Shapiro, Allison; Johnson, Susan
Abstract: Objectives: Caregiver feeding styles differ in their responsivity and thereby shape children's early feeding experiences. Laissez-faire feeding beliefs and practices are less engaged than the responsive feeding style. This study aimed to examine how the mothers' infant feeding beliefs and behaviors are associated with infant/toddler consumption of a lipid nutrient supplement (LNS). Methods: Mothers ( n  = 56) and children (7–11.30 mo infants, n  = 16; and 12–24 mo toddlers, n  = 40; toddlers) participated in a randomized, 2-week home exposure study and 2 laboratory visits ([V1] & [V2]). At both laboratory visits, mothers offered LNS until the parent determined the child was finished. Total intake (g) at V1 and V2 was measured. In the 2-week period between V1 and V2, mothers were given 10 samples of LNS to offer to their child and intake at each home feeding. Mothers also completed the Infant Feeding Styles Questionnaire (IFSQ), a self-report instrument designed to measure maternal feeding beliefs and behaviors. Spearman's correlations and independent-samples t-tests were conducted to relate mothers' feeding beliefs and behaviors to the children's intake at V1, V2, and during home feeding. Follow up comparisons of infant and toddler associations were performed with Fisher's z statistic. Significance was defined as P  < 0.05. Results: Fifty-five dyads (98%) completed V1, V2 and home feeding protocols. Higher caregiver Laissez-Faire (LF) belief scores were negatively associated with child LNS consumption for infants at V1 ( r = −0.544, P  = 0.031) but not for toddlers ( r = −0.031, P  = 0.847; Fisher's z = −1.795, P  = 0.036). Likewise, associations between LF behaviors and infant LNS intake at both V1 and V2 were significant (r V1 = −0.616, P  = 0.011, r V2 = −0.522, P  = 0.046) but not for toddlers (rV1  = 0.16, P  = 0.920, Fisher's z V1 = −2.28, P  = 0.011; r V2 = −0.191, P  = 0.237, Fisher's z V2 = −2.40, P  = 0.008). Conclusions: The LF feeding style may play an important role for infant LNS consumption. Feeding styles that are less responsive and reflect lower caregiver interaction during feeding, may be less effective in promoting children's opportunity to engage with new foods and may not facilitate their ability to learn to like LNS. Funding Sources: Global Alliance for Improved Nutrition.